Variable Abundance and Distribution of Wolbachia and Cardinium Endosymbionts in Plant-Parasitic Nematode Field Populations - Wasala, Sulochana K.; Brown, Amanda M. V.; Kang, Jiwon; Howe, Dana K.; Peetz, Amy B.; Zasada, Inga A.; Denver, Dee R. (Frontiers in Microbiology, 2019)
The bacterial endosymbiont Wolbachia interacts with different invertebrate hosts, engaging in diverse symbiotic relationships. Wolbachia is often a reproductive parasite in arthropods, but an obligate mutualist in filarial nematodes. Wolbachia was recently discovered in plant-parasitic nematodes, and, is thus far known in just two genera Pratylenchus and Radopholus, yet the symbiont’s function remains unknown. The occurrence of Wolbachia in these economically important plant pests offers an unexplored biocontrol strategy. However, development of Wolbachia-based biocontrol requires an improved understanding of symbiont-host functional interactions and the symbiont’s prevalence among nematode field populations. This study used a molecular-genetic approach to assess the prevalence of a Wolbachia lineage (wPpe) in thirty-two field populations of Pratylenchus penetrans. Populations were examined from eight different plant species in Washington, Oregon, and California. Nematodes were also screened for the endosymbiotic bacterium Cardinium (cPpe) that was recently shown to co-infect P. penetrans. Results identified wPpe in 9/32 and cPpe in 1/32 of P. penetrans field populations analyzed. No co-infection was observed in field populations. Wolbachia was detected in nematodes from 4/8 plant-hosts examined (raspberry, strawberry, clover, and lily), and in all three states surveyed. Cardinium was detected in nematodes from mint in Washington. In the wPpe-infected P. penetrans populations collected from raspberry, the prevalence of wPpe infection ranged from 11% to 58%. This pattern is unlike that in filarial nematodes where Wolbachia is an obligate mutualist and occurs in 100% of the host. Further analysis of wPpe-infected populations revealed female-skewed sex ratios (up to 96%), with the degree of skew positively correlating with wPpe prevalence. Uninfected nematode populations had approximately equal numbers of males and females. Comparisons of 54 wPpe 16S ribosomal RNA sequences revealed high similarity across the geographic isolates, with 45 of 54 isolates being identical at this locus. The complete absence of wPpe among some populations and low prevalence in others suggest that this endosymbiont is not an obligate mutualist of P. penetrans. The observed sex ratio bias in wPpe-infected nematode populations is similar to that observed in arthropods where Wolbachia acts as a reproductive manipulator, raising the question of a similar role in plant-parasitic nematodes.